Internalisasi Nilai-nilai Akhlak dalam Dasa Dharma di Kegiatan Kepramukaan - Wenda Permata Sari; Dhita Ayomi Purwaningtyas; Dilla Ayuna Letri; Dora Tiara (Prodi Pendidikan Keagamaan Islam, 2026)
This study aims to analyze the process of internalizing moral values contained in the 8th Dasa Dharma, namely “Discipline, Courage, and Loyalty,” through scouting activities at SMK Negeri 1 Kota Solok. The background of this research is based on the importance of character building among students through extracurricular activities integrated with moral values. Scouting, as a form of non-formal education, plays a strategic role in instilling the values of discipline, courage, and loyalty through structured and continuous activities.This research employs a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research subjects consisted of scout leaders and students actively involved in scouting activities. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation.The results of the study indicate that the internalization of moral values in the 8th Dasa Dharma is carried out through three stages: value transformation, value transaction, and transinternalization. The value of discipline is instilled through habituation of punctuality and adherence to rules. The value of courage is developed through training activities, competitions, and decision-making within scout teams. Meanwhile, loyalty is reflected in commitment to duties, responsibility, and dedication to the scouting organization. The role modeling of scout leaders and consistent habituation are the main factors contributing to the success of this internalization process.Thus, scouting activities at SMK Negeri 1 Kota Solok play an effective role in shaping students’ character in accordance with the moral values of the 8th Dasa Dharma.